2015
DOI: 10.15407/internalmed2015.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Opinions on Family Doctor Accessibility in Estonia

Abstract: Питання організації охорони здоров'я One of the cornerstones of the Estonian health care reforms has been the reorganization of the pri mary level medical care. It was started in 1991 by commencing training for family doctors [1, 2]. Since 1993, the list of medical specialties in Estonia also contains family medicine, and by the present time more than 800 family doctors have been trained. In 1998 a new financing scheme for family doctors came into force, foreseeing the establishment of patient lists. It introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Further studies demonstrated a rather high satisfaction as well. For example, in 2002 the satisfaction rate with the FDs was 87% [23] and most of the patients were admitted within two days [24]. Today, further evaluations of the Estonian PHC system have demonstrated rather high patient satisfaction and acceptability of the new system, however, the satisfaction with and acceptability of PHC services and FDs has been higher in patients living outside the capital, in older patients and in patients with multimorbidity [21,23,[25][26][27].…”
Section: Patient Satisfaction and Acceptability Of Phc Systemmentioning
confidence: 99%
“…Further studies demonstrated a rather high satisfaction as well. For example, in 2002 the satisfaction rate with the FDs was 87% [23] and most of the patients were admitted within two days [24]. Today, further evaluations of the Estonian PHC system have demonstrated rather high patient satisfaction and acceptability of the new system, however, the satisfaction with and acceptability of PHC services and FDs has been higher in patients living outside the capital, in older patients and in patients with multimorbidity [21,23,[25][26][27].…”
Section: Patient Satisfaction and Acceptability Of Phc Systemmentioning
confidence: 99%
“…The progress of PC reform in Baltic countries has been examined in several studies. There are a number of studies about the Estonian PC system, explaining access to PC services [13], patient satisfaction and acceptability of the PC system [11,14] as well as economic aspects of PC reform [15,16]. The studies about PC reforms in Latvia and Lithuania primarily focus on patient satisfaction and acceptability of the PC system [17][18][19][20].…”
Section: [Table 1]mentioning
confidence: 99%